Use of a Case Definition Approach to Identify Cancer-Related Fatigue in Women Undergoing Adjuvant Therapy for Breast Cancer - Andrykowski, Michael A. (2005)
PURPOSE: Use a proposed case-definition approach to identify the prevalence of cancer-related fatigue (CRF), demographic, clinical and psychosocial predictors of subsequent CRF, and psychosocial factors associated with concurrent CRF. PATIENTS AND METHODS: Women (n = 288) undergoing adjuvant therapy for early-stage breast cancer were recruited from two outpatient clinics. Women completed a baseline assessment before adjuvant therapy and a post-treatment assessment at the conclusion of an initial course of adjuvant chemotherapy or radiotherapy. At both assessments, women completed a clinical interview and measures of fatigue, distress, coping, and quality of life (QOL). The clinical interview consisted of modules from the Diagnostic and Statistical Manual of Mental Disorders Fourth Edition (DSM-IV) and a diagnostic interview to identify cases of CRF. RESULTS: CRF prevalence at the baseline and post-treatment assessments was 10% and 26%, respectively. Multivariate analyses identified factors prospectively associated with greater risk for CRF at the post-treatment assessment, including receipt of adjuvant chemotherapy and a tendency to catastrophize in response to fatigue. Patients with and without CRF differed on a host of concurrent measures of fatigue, depression, functioning, and QOL with mean effect sizes in the range of 1.0 standard deviation. CONCLUSION: CRF is a clinical syndrome experienced before and during adjuvant therapy for breast cancer. Results suggest CRF has a multifactorial etiology and support use of the proposed case definition approach to defining CRF. Future research is necessary to determine the scientific value of these criteria for understanding the etiology and management of fatigue in the oncology setting.